Influence of ligand field on magnetic anisotropy in a family of pentacoordinate CoII complexes. Issue 15 (25th March 2020) - Acharya, Joydev; Sarkar, Arup; Kumar, Pawan; Kumar, Vierandra; Flores Gonzalez, Jessica; Cador, Olivier; Pointillart, Fabrice; Rajaraman, Gopalan; Chandrasekhar, Vadapalli
Abstract : Three pentacoordinate Co II complexes were synthesized using a common tridentate ligand and varying the halide/pseudohalide ligand. The effect of the latter on the geometry and magnetic properties of the three complexes has been analysed. Abstract : A family of mononuclear penta-coordinated Co II complexes, [Co(L)Cl2 ]·CH3 OH (1 ), [Co(L)Br2 ] (2 ) and [Co(L)(NCS)2 ] (3 ) (where L is 1-mesityl- N, N -bis(pyridin-2-ylmethyl)methanamine) were synthesized and characterized. In these complexes, the neutral non-planar ligand, L, binds to three coordination sites around the metal center while two others are bound by anionic halide/pseudo halide ligands. The coordination geometry of the complexes is dictated by the coordinated anionic ligands. Thus, the coordination geometry around the metal ion is distorted trigonal bipyramidal for complexes 1 and 3, while it is distorted square pyramidal for complex 2 . Ab initio CASSCF/NEVPT2 calculations on the complexes reveal the presence of an easy plane magnetic anisotropy with the D and E / D values being, 13.3 and 0.14 cm −1 for 1 ; 36.1 and 0.24 cm −1 for 2 and ±8.6 and 0.32 cm −1 for 3 . These values are in good agreement with the values that were extracted from the experimental DC data. AC magnetic measurements reveal the presence of a field-induced slow relaxation of magnetization. However, clear maxima in the out-of-phase susceptibility curves were not observed for 1 and 3 . For complex 2, peak maxima were observed when the measurements were carried out under an applied field of 1400 Oe which allowed an analysis of the dynamics of the slow relaxation of magnetization. This revealed that the relaxation is mainly controlled by the Raman and direct processes with the values of the parameters found to be: B = 0.77(15) s −1 K −6.35, n = 6.35(12) and A = 3.41(4) × 10 −10 s −1 Oe −4 K −1 and m = 4 (fixed). The ab initio calculation which showed the multifunctional nature of the electronic states of the complexes justifies the absence of zero-field SIM behaviour of the complexes. The magnitude and sign of the D and E values and their relationship with the covalency of the metal–ligand bonds was analysed by the CASSCF/NEVPT2 as well as AILFT calculations.